Neutrophil extracellular traps in rheumatoid arthritis: pathogenic mechanisms and therapeutic potential - Mao, Cheng-Liang; Yu, Chen-Huan; Jiang, Song-Lin; Ying, Zhen-Hua; Zhu, Xing-Yi (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease marked by synovial inflammation, joint destruction, and systemic complications, eventually leading to a high rate of disability, but its exact pathogenesis remains unclear. Neutrophil extracellular traps (NETs) are chromatin fibers released by activated neutrophils during infection/inflammation, containing histones, antimicrobial proteins, and granule components. Under physiological conditions, NETs trap pathogens and act as a pivotal anti-infective mechanism of the innate immune response. During the development of RA, NET components act as danger-associated molecular patterns (DAMPs) to activate NLRP3 inflammasomes and the complements in effector lymphocytes, amplifying inflammation; NETs promote the RA-related autoantibody production in B cells, such as anti-citrullinated protein antibodies (ACPAs) and rheumatoid factor (RF), fueling autoimmunity, while ACPAs further induce NETosis, creating a vicious feedback loop; NETs facilitate the release of pro-inflammatory cytokines (e.g., IL-6, IL-1β, TNF-α), exacerbating joint damage; finally, NETs activate T cells, dendritic cells, and macrophages via boosting RAGE/TLR9 pathway, thereby driving the proliferation and migration fibroblast-like synoviocytes. Notably, inhibiting NET formation (e.g., FcαRI antibody, celastrol), blocking NET-mediated inflammation (e.g., RAGE/TLR9 antagonists), and clearing NET remnants to break the pathogenic cycle (e.g., PAD enzyme inhibitors, DNase I and CD19 CAR-T trials) provide novel strategies for RA treatment. This article highlights the pathogenic role of NETs in RA, and emphasizes the potential as clinical biomarkers and therapeutic targets for RA progression. It will open avenues for novel treatments targeting NETosis or its downstream effects, potentially improving outcomes for RA and other inflammatory arthritides.